A rare case report of rosemary-induced anaphylaxis - Sara Nogueira Machado; Cecília Gomes Pereira; Teresa São Simão; Marta Santalha; Armandina Silva; Paula Alendouro (Alergologia Polska)
Unlike allergic contact dermatitis, food allergy and anaphylaxis caused by rosemary are not well documented. This report details a distinctive case of rosemary-induced anaphylaxis in a 16-year-old female, triggered by topical application of Acarilbial ® (benzyl benzoate plus excipients, namely rosemary oil). Prick-to-prick skin tests with rosemary and an open controlled application testing with Acarilbial ® yielded positive reactions. Subsequent anaphylactic reactions, following rosemary exposure through ingestion, inhalation, and skin contact, confirmed the allergy diagnosis. To our knowledge, this report describes the first known case of rosemary-induced anaphylaxis in a pediatric patient. Recognizing the causal agent is crucial for preventing recurrences in this severe form of allergic disease.